De Sint-Servaaskerk te Maastricht in de vroege middeleeuwen (Bulletin KNOB, 1991)
Till recently only very concise sources revealed something on the previous collegiate, now parish church of St. Servatius' predecessors. Thus Gregorius of Tours (538/9-594/5) mentions a wooden tomb house on the site of the grave of Bishop Servatius (departed about 380) and, to Servatius' honour, the erection of a templum magnum by Bishop Monulf in the second half of the 6th century. During the 9th century the Gesta sanctorum patrum Fontanellensis coenobii describe a monastery 'beati Servatii', to which Abbot Wando from Saint-Wandrille has been exiled in 719. Although suspect 11th century sources mention Charles Martell's building activities in the same times (after 726) we are not informed on the accessory church.First known abbots are Alkuin and Einhard. In 889 the church and abbey were handed over to the diocesan church of Trier by King Arnulf. Till about 1000 relations of property change. The St. Servatius was insured to be sepulture of the Carolingian duke Charles of Low Lorraine (993?) and his son Otto (1006). A consecration of the church has not been transmitted before the 12th of August 1039. This consecrated nucleus of the present church underwent radical alterations in the 11th, 12th and 15th century. Research of the building's history and excavations both could not bring to light the history of the pre-Romanesque church. Only the barrel vaulted sepulchre of St. Servatius - the Confessio - with corresponding small crypt had been defined as dating from this early period, erroneously as we will see.From 1981 on a far-reaching restoration offered the opportunity to extensive excavations at the double chapel (treasure-house) on the northern side of the transept and from 1985/89 at the church itself. The authentic cella memoriae of St. Servatius and three of the church's predecessors have been discovered. In 1988 a leaden funeral cross was found in the grave of dean Humbertus (1051-1086). The inscriptions on this cross inform us of the Servatius' renovations by Humbertus extensively. Meanwhile excavations have been completed. According to present-day views the sequence of structural alterations took place as follows.Below the north-west part of the confessie (11th century) an almost square building or tomb house has been excavated, situated on the southern border of a late-antique cemetery. These remainings have been identified with the original building over the grave of St. Servatius. The templum magnum of Bishop Monulf (second half of the 6th century) was discovered outside the walls of the crossing-crypt of the Romanesque building. Fragmentary foundations of a western annexe correspond with a symmetrically reconstructed tripartite west-choir from the second quarter of the 7th century. Parts of contemporary houses for clergymen are excavated to the north below transept and Romanesque double chapel.After demolition of this templum magnum a more westerly situated basilica was erected. The shape of the choir of this three-aisled basilica is not known, but it had a crypt. The excavated 'terrazzo' pavements belong to later alterations (9th/10th century). Traces of choir screens or cancelli, which represent three successive building phases, are discovered in the eastern part of the nave. A unique relief (circa 750) with a representation of the Flight to Egypt and the Massacre of the Innocents could be coming from one of the eldest choir screens. The sepulchre of the founders of the church, Monulf and Gondulf, to the west in the axis of the church was not constructed before the 10th century.The three-aisled basilica-nave has been lengthened to the west in the 10th century as well. The basilica however was demolished completely about the end of the 10th century. Then a new three-aisled church with a cross-aisle with polygonally closed arms and ambulatory was erected, corresponding with the nucleus of the present-day church. The ground-plan of choir with east-crypt, the Confessio and the substructure of westwork and western choir date from the same period and can be connected with the consecration of 1039. According to the inscription on his funeral cross dean Humbertus rebuilt both eastern and western part of the church and executed many new constructions on the cloistral court as well. The whole church was vaulted in the 15th century. The chapels of the side-aisles and a new cloister have been laid out in the same age.